Hubungan Antara Stres Kerja Dengan Komitmen Organisasi Pegawai Dinas Ketenagakerjaan Kabupaten Deli Serdang - Muhammad Rangga; Azhar Aziz (Mahesa Research Center, 2026)
This study aimed to determine the correlation between work stress and organizational commitment among employees of the Department of Manpower of Deli Serdang Regency. This study employed a quantitative approach with a correlational research method. The population consisted of 30 employees, all of whom were selected as research participants using the total sampling technique. Data were collected using a work stress scale and an organizational commitment scale. The data were analyzed using the Pearson Product-Moment Correlation technique with the assistance of IBM SPSS Statistics version 23.0. The results showed a significant negative correlation between work stress and organizational commitment, with a correlation coefficient of r = -0.685 and a significance value of p = 0.000 (p < 0.05). These findings indicate that the higher the level of work stress experienced by employees, the lower their organizational commitment. The coefficient of determination analysis revealed an R Square value of 0.469, indicating that work stress contributed effectively 46.9% to organizational commitment. Therefore, the research hypothesis was accepted, and work stress was proven to be significantly correlated with organizational commitment among employees of the Department of Manpower of Deli Serdang Regency.